Uji Antibakteri Ekstrak Etanol Akar Tawas Ut (Ampelocissus Rubiginosa Lauterb) pada Eschericia Coli dan Staphylococcus aureus Secara In Vitro: In Vitro Antibacterial Test of Ethanol Extract of Ut Tawas Root (Ampelocissus Rubiginosa Lauterb) on Eschericia Coli and Staphylococcus aureus - Eka Khaharap (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
The used of antibiotics to control bacterial growth has a negative impact such as antibiotics resistance. Began to look for alternative materials from nature, including saponins, flavonoids, catechins and tannins which are known to be contained in the roots of Tawas Ut (Ampelocissus rubiginosa Lauterb). This plant has been used empirically by the people of Central Kalimantan, namely as a medicine for wounds and diarrhea. The efficacy of alum root has not been scientifically proven. The antibacterial properties of this plant have the potential as a source of antibacterial compounds for the growth of E. coli and S. aureus in vitro. The research method used was the Kirby Bauer Antibacterial Testing method. The ethanol extract of alum ut root has antibacterial activity against E. coli and S. aureus, with an extract concentration of 250 mg∙ml-1 giving the highest average clear zone value of 12.33 mm in E. coli and S. aureus, and was able to give a clear zone with the lowest concentration of 12.5 mg∙ml-1 of 11.33 mm in E. coli and 11.67 mm in S. aureus. The minimum inhibitory concentration (MIC) of ut alum root ethanol extract on E. coli and S. aureus was 15.6 mg∙ml-1.